Alloimmunisation during pregnancy in Greece: need for nationwide HDFN prevention programme. Issue 4 (5th July 2013) - Foudoulaki‐Paparizos, L.; Valsami, S.; Bournas, N.; Tsantes, A.; Grapsas, P.; Mantzios, G.; Travlou, A.; Politou, M.
SUMMARY Aim/Objectives To access the incidence and specificity of maternal red blood cells alloimmunisation and its relevant clinical impact in Greece. Background The rate of alloimmunisation in pregnant women in Greece is unknown. Materials/Methods We performed a 4‐year study in two tertiary hospitals in Greece. Demographics, transfusion and obstetric history were analysed. Maternal alloimmunisation was detected with indirect anti‐globulin test. Results We investigated 4368 pregnant women. Of which 3292 (75·37%) were Greek and 1076 (24·63%) were migrants. In 39 alloimmunised women, 41 alloantibodies were detected (0·89%). The incidence of alloimmunisation was 0·66% (22/3292) in Greeks and 1·76% (17/1076) in migrants (P = 0·01). Anti‐D was the most frequent alloantibody (0·18%). Anti‐D was more frequent in migrants; 5·76% compared to 0·56% in Greek RhD negative women (P = 0·002). Other antibody specificities in declining frequency rank were anti‐K, anti‐E, anti‐Lea, anti‐M, anti‐c, anti‐Ce, anti‐Jka, anti‐Jkb and anti‐C. Primiparae vs para >2 and past history of blood transfusion were significantly associated with alloimmunisation during pregnancy (P = 0·0088, P < 0·0001, respectively). Conclusions Our results depict differences in the delivery of health care between migrants and Greek women, as well as the heterogeneity in practices for the prevention of haemolytic disease of foetus and newborn in Greece and highlight the need for the implementation of nationwide guidelines.